The Dreamers and DACA - Harris, Duchess; Katz, Nina Judith (Special reports (Essential Library (Firm)), 2019)
Examines Dreamers and DACA, the Obama-era bill that allows for forgiveness for immigrants who were brought to the United States as children and whose legal status may be in question. Contains sidebars that place the events within the larger context of race, civil rights, and immigration in America, and topics that have become a political hot-button issue for all political parties. Includes a glossary, resources for further information, and color photographs.